The influence of islamic video content on the formation of halal awareness: an analysis of muslim consumer behavior based on the theory of planned behavior - Supriati Hardi Rahayu; Muthmainnah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze the influence of religious video content on the halal awareness (al-wa’yu al-halal) of Muslim consumers in Indonesia by integrating the Theory of Planned Behavior (TPB) and the principles of maqashid sharia. A quantitative approach with an explanatory survey design was employed, involving 300 Muslim respondents aged 18–35 years who actively accessed religious video content on social media. Data were analyzed using Structural Equation Modeling (SEM) with AMOS, including validity, reliability, and goodness of fit testing. The findings indicate that religious video content significantly influences halal attitudes (β = 0.200, p = 0.003), subjective norms (β = 0.175, p = 0.006), and behavioral control (β = 0.172, p = 0.009). Behavioral control emerged as the strongest predictor of purchase intention (β = 0.283, p < 0.001), followed by subjective norms (β = 0.217, p = 0.001) and halal attitudes (β = 0.171, p = 0.022). Purchase intention significantly influenced actual halal consumption behavior (β = 0.274, p < 0.001). This study highlights the strategic role of video-based digital da’wah in enhancing halal literacy and offers practical contributions for preachers, educators, and policymakers to design content that is accurate, engaging, and relevant to younger generations. Theoretically, this research integrates TPB with maqashid sharia and develops a fiqh-based da’wah content evaluation matrix, which remains rarely found in international literature.